2020
DOI: 10.3390/ijms21124239
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Metformin Use in Diabetic Kidney Disease

Abstract: Metformin is a glucose-lowering agent that is used as a first-line therapy for type 2 diabetes (T2D). Based on its various pharmacologic actions, the renoprotective effects of metformin have been extensively studied. A series of experimental studies demonstrated that metformin attenuates diabetic kidney disease (DKD) by suppressing renal inflammation, oxidative stress and fibrosis. In clinical studies, metformin use has been shown to be associated with reduced rates of mortality, cardiovascular disease and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 101 publications
(120 reference statements)
1
37
0
2
Order By: Relevance
“…The impact of metformin on the kidney in diabetics is also a consequence of both its glucose lowering-dependent and glucose-independent mechanism [ 230 ]. The toxic effect of hyperglycemia on the kidney is well recognized both in animal models and in humans.…”
Section: Clinical Aspects Of Metforminmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of metformin on the kidney in diabetics is also a consequence of both its glucose lowering-dependent and glucose-independent mechanism [ 230 ]. The toxic effect of hyperglycemia on the kidney is well recognized both in animal models and in humans.…”
Section: Clinical Aspects Of Metforminmentioning
confidence: 99%
“…Hyperglycemia increasing oxidative stress and generation of free radicals, inducing low-grade chronic inflammation, and autophagy is responsible for podocyte damage and its death and for the intensification of tubule-interstitial fibrosis. Therefore, metformin with its potent anti-hyperglycemic effect, inhibition of advanced glycation end products accumulation in various tissues and decreasing hyperglycemia -related inflammation and oxidative stress may slow down all these kidney damaging processes [ 229 , 230 , 231 ]. Experimental studies on mammalian cells have shown that metformin increases the level of anti-aging protein (klotho protein) which may inhibit the progression of various kidney diseases.…”
Section: Clinical Aspects Of Metforminmentioning
confidence: 99%
“…As in other tissues, also in the kidney metformin acts via both AMPK-dependent and -independent pathways as described in the following paragraphs, in which I will concentrate on the effects of metformin in podocytes. For comprehensive reviews covering the effects of metformin in the kidney beyond podocytes, see the following recent review articles [ 93 , 94 , 95 , 96 , 97 ]. The mechanisms of action of metformin in different tissues are reviewed in [ 98 ].…”
Section: Mechanisms Whereby Metformin Reduces Hyperglycaemiamentioning
confidence: 99%
“…Metformin also ameliorates the senescence of renal tubular cells in culture and in diabetic db/db mice by up-regulating miR-130a-3p and down-regulating STAT3, a target gene of miR-130a-3p involved in the pathogenesis of DKD [ 136 ]. For recent reviews on the beneficial effects of metformin in the kidney at large, the readers are referred to [ 93 , 94 , 95 , 96 , 97 ].…”
Section: Podocyte-protective Mechanisms Of Action Of Metforminmentioning
confidence: 99%
See 1 more Smart Citation